OPTIMIZATION OF RED PIGMENT PRODUCTION BY MONASCUS PURPUREUS FTC 5356 USING RESPONSE SURFACE METHODOLOGY - M. Said, Farhan; Hamid, Nor Farhana Binti (IIUM Engineering Journal, 2018)
Factors such as environmental conditions and nutrients are significant for successful growth and reproduction of microorganisms. Manipulations of the factors are the most effective way to stimulate the growth of the microorganism, which can be used to optimize the yield of a product. In this study, Central Composite Design (CCD) of Response Surface Methodology (RSM) was used to optimize the production of red pigment by Monascus purpureus FTC 5356 using the petioles of oil palm fronds (OPF) as a substrate in solid state fermentation (SSF). The data was analyzed using Design Expert Software. The optimum combination predicted via RSM was confirmed through experimental work. The interactions between three variables such as initial moisture content (%), initial pH value (pH), and peptone concentration (%) were studied and modelled. The statistical analysis of the results showed that the optimal conditions for red pigment production 47 AU/g with the biomass of 425.1 mg/g was at 55% initial moisture content, 3% of peptone, and at pH 3.Â The RSM results showed that the initial pH value had a significant effect on red pigment production (P-value <0.05). The validation of these results was also conducted by fermentation with predicted conditions and it was found that there was a discrepancy of 0.39% between the values of the experimental result and those of the predicted values. ABSTRAK: Keadaan persekitaran dan nutrien merupakan faktor-faktor penting dalam pertumbuhan mikroorganisma. Manipulasi faktor-faktor tersebut adalah kaedah terbaik bagi meningkatkan pertumbuhan mikroorganisma dan mengoptimumkan penghasilan produk. Kajian ini mengguna pakai Rekaan Gabungan Pusat (CCD) melalui Kaedah Tindak balas Permukaan (RSM) bagi penghasilan pigmen merah optimum oleh Monascus purpureus FTC 5356 menggunakan batang pelepah kelapa sawit (OPF) sebagai perumah dalam proses penapaian pepejal (SSF). Data telah dianalisis menggunakan perisian Design Expert. Gabungan parameter optimum seperti cadangan RSM telah disahkan secara eksperimen. Interaksi antara tiga pemboleh ubah seperti kandungan lembapan awal (%), nilai pH awal (pH), dan kepekatan pepton (%) telah dikaji dan dimodelkan. Analisis statistik menunjukkan penghasilan optimal pigmen merah adalah pada 47 AU/g dengan biomas sebanyak 425.1 mg/g, pada 55% lembapan awal, 3% pepton dan pada pH 3. Hasil keputusan RSM menunjukkan pH awal memberikan kesan signifikan kepada penghasilan pigmen merah (nilai P <0.05). Pengesahan analisis juga telah dijalankan melalui proses penapaian dan hasil ujikaji mendapati 0.39% lebih tinggi daripada nilai jangkaan.